Local Epidemiology of Nosocomial Staphylococcus aureus Infection in a Nigerian University Teaching Hospital - Adeniran Adeyanju; Frieder Schaumburg; Adedeji Onayade; Akinyele Akinyoola; Taofeeq Adeyemi; Osaretin Ugbo; Robin Köck; Yemisi Amusa; Oladejo Lawal; Temilade Adeyanju; Nkem Torimiro; David Akinpelu; et al. (Antibiotics, 2022)
Population-based studies of Staphylococcus aureus contribute to understanding the epidemiology of S. aureus infection. We enrolled surgical inpatients admitted to an African tertiary-care hospital in order to prospectively analyze the nosocomial impact of S. aureus. Data collection included an active sampling of the anterior nares and infectious foci within 48 h after admission and subsequently when clinically indicated. All S. aureus isolates were spa and agr genotyped. Possession of Panton-Valentine leukocidin (PVL) and other toxin genes was determined. We analyzed antibiotic susceptibility profiles by VITEK 2 systems and verified methicillin-resistant S. aureus (MRSA) by mecA/C PCR. Among 325 patients, 15.4% carried methicillin-susceptible S. aureus (MSSA) at admission, while 3.7% carried MRSA. The incidence densities of nosocomial infections due to MSSA and MRSA were 35.4 and 6.2 infections per 10,000 patient-days, respectively. Among all 47 nosocomial infections, skin and soft-tissue (40.4%) and bones or joints’ (25.5%) infections predominated. Six (12.7%) infection-related S. aureus isolates harbored PVL genes including two (4.2%) MRSA: overall, seventeen (36.2%) isolates carried pyrogenic toxin superantigens or other toxin genes. This study illustrates the considerable nosocomial impact of S. aureus in a Nigerian University hospital. Furthermore, they indicate a need for effective approaches to curtail nosocomial acquisition of multidrug-resistant S. aureus.